Pengembangan Multimedia Interaktif Menggunakan 3D Pageflip Professional pada Materi Penentuan Jenis Kelamin Serangga untuk Kelas XII SMA: Development of Interactive Multimedia Using 3D Pageflip Professional on Insect Gender Determination Materials for Class XII SMA - Yusar Rahmi; Asni Johari; Ali Sadikin (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
This study aims to develop interactive multimedia-based learning media using 3D Pageflip Professional. The developed media discuss material about determining the sex of insects, this research belongs to the Research and Development (R & D) type using the ADDIE method. The research was conducted at SMA N 10 Jambi City in September 2021. The research data was obtained by distributing questionnaires via google form to students and teachers of biology subjects. Data analysis techniques were carried out qualitatively and quantitatively. The results of validation by material experts and media experts stated that this media was categorized as